A Comprehensive Review of Big Data’s Role in Risk Management and Security: A Bibliometric Approach - Muthohirin, Muthohirin (International Economic Conference of Business and Accounting, 2024)
This study conducted a literature review on the role of big data in risk management and security. The researchers used bibliometric methods to analyze 114 articles from Scopus-indexed journals. The findings revealed a steady increase in publications since 2005, with a peak in 2022. The most influential journals in this field were identified as Procedia Computer Science and IEEE Access. Several authors, including Babar M, Chang V, He X, Li Z, Li Y, Liu S, and Saxby S, were recognized as key influencers. Notably, China, India, and the United States were prominent in publications related to big data in risk management and security. Based on the thematic map generated by the research, future studies are recommended to focus on privacy design, data security systems, data privacy, information management, and risk assessment. This research provides valuable insight into the role of big data in improving organizational security and risk management.